2021
DOI: 10.1186/s12876-021-01976-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of macrogol 4000 plus electrolytes in bowel preparation for colonoscopy in patients with chronic constipation

Abstract: Background Chronic constipation is a significant factor in poor bowel preparation for colonoscopy. Macrogol 4000 plus electrolytes (Movicol, EA Pharma, Tokyo, Japan), containing polyethylene glycol (PEG) and electrolytes, have been used recently to treat patients with constipation. However, prospective studies on the use of macrogol 4000 for bowel cleansing for colonoscopy are lacking. This study aimed to investigate the efficacy and safety of macrogol 4000 in addition to PEG administered in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…According to a 2019 RCT[ 100 ], the optimal dose of crystalline lactulose for Japanese constipated patients is 26 g/day. A short therapy cycle of PEG plus electrolytes was effective and safe in improving bowel preparation in chronic constipation patients in a 2020 and 2021 Japanese study[ 101 , 102 ]. In 2016, a larger Asian population was studied in a randomized, double-blind, placebo-controlled trial[ 103 ].…”
Section: Specific Clinical Settingsmentioning
confidence: 99%
“…According to a 2019 RCT[ 100 ], the optimal dose of crystalline lactulose for Japanese constipated patients is 26 g/day. A short therapy cycle of PEG plus electrolytes was effective and safe in improving bowel preparation in chronic constipation patients in a 2020 and 2021 Japanese study[ 101 , 102 ]. In 2016, a larger Asian population was studied in a randomized, double-blind, placebo-controlled trial[ 103 ].…”
Section: Specific Clinical Settingsmentioning
confidence: 99%
“…Polyethylene glycol electrolytes (PEG) are widely used as bowel cleansers during colonoscopy ( 8 ), but the PEG regimens alone remain unsatisfactory in patients with chronic constipation (CC) because of dose intolerance. A study showed that compared with the 4L-PEG regimen, 2L-PEG plus bisacodyl improved colonic mucosa visualization, patient acceptance, and compliance in patients with CC, but did not increase the bowel cleansing efficiency ( 9 ).…”
Section: Introductionmentioning
confidence: 99%